Cooling of a heated surface in spray chamber - Ang, Samuel Qi Xiang (2019)
With the rising demand for faster heat removal techniques in cooling high powered electronic devices, spray cooling has been shown to be an effective cooling system that is capable of high heat flux removal. The present study investigates the individual effects of flow rate, power and liquid type, namely water and Novec 7100, on spray cooling in a closed loop. The spray chamber consists of six nozzles that are capable of spraying a flow rate of up to 0.4 LPM on a heated surface that measures 233 by 160 by 10 mm. Results of spray cooling were optimistic as there is an immediate and visible drop in temperature once the pump driving the liquid was initiated. It was revealed that the heat transfer coefficient increases with flow rate almost linearly in the water spray cooling experiments. For the experiments conducted with higher heating power, higher heat transfer coefficients were also obtained. Furthermore, the location of the nozzle was found to be a crucial parameter in achieving better spray cooling as the surface thermocouple that is located directly adjacent to two different nozzles clocked the lowest temperatures among all the thermocouples. In a similar setup conducted with the same power and flow rate, Novec 7100 produced a poorer heat transfer coefficient than water as Novec 7100 has a lower specific heat capacity. It was concluded that Novec 7100 requires higher flow rates or heating power to match the heat transfer coefficient of water.